Maternal Stimulation Upon Mother‐Infant Face‐to‐Face Interaction - Supra Wimbarti (Buletin Psikologi, 2006)
Mother‐infant relation is very unique. Research on mother‐infant interaction has dated back in the 1970s. Stern (1971) stated that there are some characteristics of mothers when they interact with their ʺinfants. The early interaction between them later in the child’s life predicts how well is the child’s interaction with other people